Highly purified natural rubber IV. Preparation and characteristics of gloves and condoms - Nakade S; Hayashi M; Kuga A; Tanaka Y (Journal of Natural Rubber Research, 1997)
Rubber gloves were produced using highly deproteinised natural rubber (HDPNR) latices with green strength comparable to that of gloves produced from a commercial high-ammonia natural rubber (HA) latex. These latices were prepared from HA latex by the method previously reported. The prevulcanisation of HDPNR latex gave characteristics which are slightly different from those of HA latex, although it did not affect the glove preparation process. The HDPNR gloves thus prepared (except chlorinated ones) satisfied the ASTM specifications for examination gloves and were superior to the gloves from HA latex in terms of softness, clarity and low odour. Condoms also were prepared from two different types of HDNPR latex; one was the above mentioned HDPNR latex and another was a HDPNR latex prepared from a prevulcanised HA latex. The condoms from these HDPNR latices were superior to those from HA latex in terms of softness, transparency, water resistence and lack of odour.
Keywords: Highly purified natural rubber